Assessment of cases of ankle arthrodesis in posttraumatic arthritis performed using Charnley's compression device - Srivastava, Deepak (International Journal of Psychosocial Rehabilitation, 2020)
Background:The ankle arthroplasty has been used to treat ankle arthritis patients. The present study was conducted to assess cases of ankle arthrodesis in posttraumatic arthritis performed using Charnley's compression device.Materials & Methods:92 cases of ankle arthritis of both genders were included. Compression was achieved using Charnley’s compression device. All the patients were assessed clinically and radiologically. American Orthopedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot scale was used.Results: Out of 92, males were 50 and females were 42. The mean ankle fusion was observed in 20.4 weeks. Indication for ankle arthrodesis was avascular necrosis (AVN) talus in 24, malunited bimalleolar fracture in 30, distal tibial plafond fractures in 10 and medial malleoli non-union in 8 cases. AOFAS results was excellent in 85, good in 4, fair in 3 cases. The difference was significant (P< 0.05).Conclusion: Ankle arthrodesis is considered as a standard procedure in ankle arthritis.